European Integration as a Social Experiment in a Globalized World - Reiner Hoffmann; Otto Jacobi; Berndt Keller; Manfred Weiss (Hans-Böckler-Stiftung, 2003)
The European Union (EU) of today is the result of a 50-year process of confidence building between countries that used to be enemies. Although it has had setbacks and periods of marking time, European integration has, on the whole, been a success story. The EU has always been so attractive that more and more European countries have joined or intend to do so. Outside Europe, the EU has long been seen as a global economic power and, it may be hoped, a political force that is increasingly becoming more active world wide and speaking with a single voice on foreign policy. Both these aspects have given the inspiration for this anthology. Part A contains three articles giving a general view. These will be of interest to those readers who wish to learn more about the process of European unification. Part B consists of articles dealing with the question whether the EU's integration potential will suffice to bind the new member states from Central Eastern Europe into the Union, or whether the reverse may happen and the eastward enlargement turn out to be a Trojan horse. The arguments about the European Social Model as a driving force or a threat are central to the discussion. The final section presents views from the outside looking in.We were interested to learn how academic observers assess the EU, and whether the European way of cross-border partnership might be a reference model for other regions of the world. During the preparation of this book, we came across an interesting phenomenon. We noted that our question received a great deal of attention, especially in the context of NAFTA (North America Free Trade Agreement) and FTAA (Free Trade Agreement of the Americas), which developed as an alternative to the European model.At the same time,we found that many observers outside Europe do not yet feel able to give a firmly-based assessment. This spurs us to give even greater priority to this question in the future, and so we present this book as a first interim result. The answers vary, but variety is the spice of life. – – Die Europäische Union strahlt eine große Attraktivität aus. Zehn Länder werden ihr im Jahre 2004 beitreten, andere stehen vor der Tür. Der Band beginnt mit Überblicksartikeln für alle, die mit der EU noch nicht so vertraut sind. Ihnen schließen sich Artikel an, die die Frage behandeln, ob die Erweiterung zu einer Zerreißprobe der EU führt oder ob sie über genügend Kraft verfügt, die neuen Beitrittsländer zu integrieren und das Europäische Sozialmodell zu festigen. Höchst interessant sind die Außensichten auf die EU. In Beiträgen aus den USA, der Türkei, Südafrika und den afrikanischen Anrainerstaaten des Mittelmeeres wird ein differenziertes Bild gezeichnet von den Schwierigkeiten im Umgang mit der EU aber auch von dem Vorbildcharakter bei der Schaffung eines transnationalen Politik- und Wirtschaftsraumes.
Keywords: 300